Molecular characterization of the NSP4 gene of human group A rotavirus samples from the West Central region of Brazil - Tavares, Talissa de Moraes (2008)
Nonstructural protein 4 (NSP4), encoded by group A rotavirus genome segment 10, is a multifunctional protein and the first recognized virus-encoded enterotoxin. The NSP4 gene has been sequenced, and five distinct genetic groups have been described: genotypes A-E. NSP4 genotypes A, B, and C have been detected in humans. In this study, the NSP4-encoding gene of human rotavirus strains of different G and P genotypes collected from children between 1987 and 2003 in three cities of West Central region of Brazil was characterized. NSP4 gene of 153 rotavirus-positive fecal samples was amplified by reverse transcriptase-polymerase chain reaction and then sequenced. For phylogenetic analysis, NSP4 nucleotide sequences of these samples were compared to nucleotide sequences of reference strains available in GenBank. Two distinct NSP4 genotypes could be identified: 141 (92.2%) sequences clustered with NSP4 genotype B, and 12 sequences (7.8%) clustered with NSP4 genotype A. These results reinforce that further investigations are needed to assess the validity of NSP4 as a suitable target for epidemiologic surveillance of rotavirus infections and vaccine development.